ANALISIS FILM OH MY GOD DENGAN AJARAN ISA UPANISAD - I Gusti Agung Ngurah Agung Yudha Pramiswara; Luh Putu Santi Pradnya Yanti; Desak Made Ayu Indri Safira (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The film is a work of art that has the completeness of several elements of art to complement the needs of a spiritual nature. The elements of art that exist and support a film include fine arts, photography, architecture, dance, literary poetry, theater, music, poetry and novels. One of the films that attract attention is the film titled Oh My God, directed by Umesh Shukla. The uniqueness of this film coupled with some very exciting debate scenes makes this a learning for the audience and encourages the writer to study the actions of the main character in accordance with the teachings of Hinduism. The most interesting part is when Kanji Lalji Mehta (Paresh Lawal) sue God to court. Are there people in the world who dare to bring God to justice? This is a difficult and crazy thing to imagine, of course, there is no human who doubts the power of God to dare to fight His power with actions that are equal to human actions. But this is what Kanji Lalji Mehta did.